Foresight for Future Planning Training Series: Information Pack - Chesterman, Sabrina; Neely, Constance (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Link to the full toolkit: https://drive.google.com/file/d/1tiJGrq9OyCA9NTLbCt__YAd3ojDnYElV/view